2003
DOI: 10.1197/jamia.m1170
|View full text |Cite
|
Sign up to set email alerts
|

Webcasting Videoconferences Over IP: A Synchronous Communication Experiment

Abstract: A multipoint videoconference was webcast live to an audience who could communicate with conference panelists and each other via chat. The videoconference, webcast, and chat were done entirely over the Internet. Seven panelists at four conference sites that had Internet2 connectivity and were located in different time zones within the continental United States discussed the topic of "Evaluating Health Professions Education and Information Resources on the Web." This discussion was broadcast to individuals and g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2005
2005
2011
2011

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 6 publications
0
10
0
1
Order By: Relevance
“…31,32 Indeed, this program addresses the development of individual skills in critical appraisal and EBM and opts for a self-tutorial method of instruction. A recent study 33 found no significant differences between two forms of EBM teaching: one consisting of directed workshops and the other consisting of a selfdirected computer-assisted program.…”
Section: Discussionmentioning
confidence: 99%
“…31,32 Indeed, this program addresses the development of individual skills in critical appraisal and EBM and opts for a self-tutorial method of instruction. A recent study 33 found no significant differences between two forms of EBM teaching: one consisting of directed workshops and the other consisting of a selfdirected computer-assisted program.…”
Section: Discussionmentioning
confidence: 99%
“…Multi-site videoconferencing generally uses voice-activated switching -a device that automatically switches the image on the screen so that only the site where the active speaker is located is shown at any given time [18]. This technique could enable higher levels of both viewer participation and engagement; however, voice activated switching could also serve to alienate participants in multi-site videoconferences by rendering them invisible.…”
Section: Multi-site Videoconferencing Viewsmentioning
confidence: 98%
“…Multi-point videoconferencing is challenging for participants used to seeing just one image on the screen as they would on a television set. Participants have greater difficultly paying attention to and looking at multiple sites displayed on one screen [18]. For large group multi-site videoconferencing a larger screen is recommended.…”
Section: Multi-site Videoconferencing Viewsmentioning
confidence: 99%
“…However, they require more technical infrastructure and can be difficult to manage [19,20]. Additionally, webinar software is designed for distance learning, which is a different method of learning than lecture interaction.…”
Section: Mobile Interaction In Learningmentioning
confidence: 99%